2017
DOI: 10.5296/ijrd.v4i2.10210
|View full text |Cite
|
Sign up to set email alerts
|

The Entrepreneurial Orientation (EO) of Incubators, Accelerators, and Co-working Spaces

Abstract: The concept of entrepreneurial orientation (EO) is widely accepted as a significant theory in the literature on firm-level entrepreneurship. Despite the collectivity of research, which continues to demonstrate that entrepreneurship and EO differ in nature and according to context, too often, context is ignored. To address this gap, this paper proposes a conceptual framework based on three suddimensions of EO (innovativeness, risk-taking and proactiveness) and a qualitative, multiple case study approach that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…Recent studies have discussed the role of these spaces in local economic development processes (Van Holm, 2017), and their relationship with entrepreneurs (Gertner & Mack, 2017). Research has also confirmed the impact of CWSs on education and employment creation (van Holm, 2015;Wang & Loo, 2017;Wolf-Powers et al, 2017), as well as the importance of entrepreneurial co-location within cities more generally (Andersson & Larsson, 2016;Witt, 2004).…”
Section: How Do We Understand Co-working Spaces?mentioning
confidence: 89%
“…Recent studies have discussed the role of these spaces in local economic development processes (Van Holm, 2017), and their relationship with entrepreneurs (Gertner & Mack, 2017). Research has also confirmed the impact of CWSs on education and employment creation (van Holm, 2015;Wang & Loo, 2017;Wolf-Powers et al, 2017), as well as the importance of entrepreneurial co-location within cities more generally (Andersson & Larsson, 2016;Witt, 2004).…”
Section: How Do We Understand Co-working Spaces?mentioning
confidence: 89%
“…From a methodological standpoint, a significant body of research has explored the new world of work through a quantitative lens. This includes research on the relation between telework and the notion of community based on the analysis of large‐scale surveys (Kamerade and Burchell, ); or more recently, Assenza's () study of entrepreneurial hackers and co‐working spaces (and how space can contribute to new venture creation) that offers a model for empirical measurement of the interaction between spatial configuration and economic outcomes; or Gertner and Mack's () exploration of the entrepreneurial orientation of different types of business support to entrepreneurs such as incubators, accelerators and co‐working spaces, and who suggest indicators for measuring different dimensions of entrepreneurial orientation. Qualitative research on the new world of work probably outnumbers its quantitative counterpart.…”
Section: Conceptual and Methodological Considerations In The Study Ofmentioning
confidence: 99%
“…Generally, accessibility by car and/or by public transport can be distinguished as relevant attribute levels. Regardless of their location, as a second distinguishing attribute coworking spaces can be located in new, modern offices but also in former industrial era warehouses (Deskmag 2016 ) with more complex structural elements (Gertner and Mack 2017 ). Early coworking spaces made use of practical furniture when setting-up typical home-like environments with couches, kitchen desks and other home-based furniture (Brown 2017 ; Neuberg 2005 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A third attribute is the layout of the space, as openness has been shown to influence face-to-face interactions in offices (Rashid et al 2006 ) and thus possibly how the social component is experienced (Bouncken et al 2020a ). Generally, coworking spaces have an open layout (Gertner and Mack 2017 ), as this is likely to stimulate interaction between coworkers as intended, but a half-open layout can also be present and even individual, closed spaces are offered in some coworking spaces (Deskmag 2016 ) to cater all possible preferences (Wright 2018 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%